Az életminőség egyenlőtlenségei az Európai Unióban = Inequalities of quality of life in the European Union - Csébi, Márk (Közép-Európai Közlemények, 2018)
European Union ranks highly in quality of life, but there are huge disparities among countries, regions and cities. In this paper I analyse these territorial inequalities with objective and subjective indicators. First of all I present in brief the history of quality of life research from ancient times up to now. It is a multidisciplinary theme, so it hasn’t got a generally accepted definition and methods, but in this study I try to give an overview the framework of quality of life. This study mainly theoretical and recapitulative. I make time comparison – highlighting the changes – with objective and subjective indicators at different territorial levels. To compare the unevenness at the level of countries I use the Human Development Index (1990–2015) and results of European Quality of Life Surveys (2003–2016). Nowadays levels of regions in European Union policies is less and less important. At this level I summarize the results of a Netherlands Environmental Assessment agency’s report (2014). Urban areas – as opposed to the regions – more and more important factors. I am city (Budapest) researcher, so I analyse the level of cities in the most detailed, focused on Budapest: Mercer’s Quality of Living Rankings, The Economist’s Liveability index.